ANALYSIS OF THE DESIGN OF A TUBE PHOTOBIOREACTOR FOR CARBON CAPTURE OF EXHAUST GAS IN SINGLE-CYLINDER ENGINE VEHICLES USING MICROALGAE - Czarthrya Indra Prastha; Boni Sena; Farradina Choria Suci; Hendra Nur Arifin (Purifikasi, 2026)
The increase in carbon dioxide (CO₂) emissions from transportation significantly contributes to global warming, necessitating innovative carbon capture solutions. This study aims to analyze the exhaust gas characteristics of a single-cylinder Otto cycle engine as a basis for designing a tubular photobioreactor for carbon capture using microalgae. The research method involves stoichiometric analysis of octane (C₈H₁₈) combustion, thermodynamic calculations of exhaust gas flow rate, and mathematical modeling of photobioreactor design parameters, including volume, illumination surface area, hydraulic retention time (HRT), Reynolds number, and CO₂ mass transfer rate. The stoichiometric combustion analysis shows that 1 mol of C₈H₁₈ produces 8 mol of CO₂, which theoretically can be fully utilized in the photosynthesis process to generate 8 mol of biomass (CH₂O). The designed tubular photobioreactor has a total volume of 3.33 liters, an illumination surface area of 0.21 m², and an HRT of 300 seconds under a flow rate of 0.67 L/min. The Reynolds number of 392 indicates laminar flow conditions, with a CO₂ transfer capacity of approximately 10.5 g/hour. These results demonstrate the potential integration of internal combustion engine exhaust gas with a tubular photobioreactor system as a small-scale carbon capture approach.